Screening and Isolation of Protease Producing Bacteria from Diabetic Foot Ulcers - Sarah Ghalib Khudhur; Saadon, Hanan; Aya Talib jawad; Jebur , Assala; Abd Ali , Abbas; Farah Al-Ali (University of Thi-Qar Journal of Science, 2024)
This study was conducted to detect bacterial causative pathogens in patients with diabetes foot ulcer infections and determine the protease enzyme. Samples were collected from 75 swabs were collected from patients suffering from diabetic foot ulcers referred to The Diabetic Center /Thi-Qar province. Data collected from patients included: age, gender and Period of infection. The results revealed that positive bacterial growth appeared in 54 (72 %) of diabetic foot ulcer specimen, and the most common isolates were Enterobacter cloaca 15(27.77%), followed by proteus mirabilis 12 (22.22%), Staphylococcus aureus 10 (18.51%), Escherichia coli 8 (14.81%), for each one Klebsiella pneumonia, Pseudomonas aeruginosa and Streptococcus pyogens 3(0.84%). The results of the Protease enzyme test were performed for all 54 isolates to determine the variable ability of these bacterial species isolated from didactic foot ulcers to produce this enzyme. The highest percentage production protease enzyme was 100 % for Pseudomonas aeruginosa, Staphylococcus aureus and 76.92% for proteus mirabilis, while the isolates showed a low production of 20.0 % for Enterobacter cloaca.